In vitro identification of the cytochrome P450 isozymes involved in the N-demethylation of the active opioid metabolite nortilidine to bisnortilidine - Wustrow, Isabel Katharina Ruth; Riedel, Klaus-Dieter; Mikus, Gerd; Weiß, Johanna (Naunyn-Schmiedeberg's archives of pharmacology, 2012)
Tilidine exhibits the highest consumption of opioids in Germany. The prodrug is hepatically metabolised in a sequential N-demethylation reaction. Its primary metabolite nortilidine is a selective μ-opioid receptor agonist which can penetrate the blood-brain barrier. Cytochrome P450 isozymes (CYP) 3A4 and CYP2C19 were previously identified as isozymes mediating the formation of nortilidine. This study was set up to identify the enzymes and kinetics of the subsequent N-demethylation to bisnortilidine, thus being able to understand clinical interactions. Human liver microsomes and recombinant CYPs were used to investigate the metabolism of nortilidine to bisnortilidine. Nortilidine and bisnortilidine were quantified using liquid chromatography tandem mass spectrometry. Inhibitor screening kits were used to quantify the inhibition of CYP3A4, CYP2C19, CYP2B6 and CYP2D6 by bisnortilidine. Nortilidine metabolism to bisnortilidine followed the Michaelis-Menten kinetics with K m = 141.6 ± 15 μM and V max = 46.2 ± 3 nmol/mg/h. Inhibitors of CYP3A4, CYP2C19 and CYP2B6 inhibited this reaction. Assays with recombinant CYPs verified that the N-demethylation is catalysed by CYP3A4, CYP2C19 and CYP2B6. Our results also demonstrated that the metabolism from tilidine to nortilidine is not only mediated by CYP3A4 and CYP2C19, but also by CYP2B6. Moreover, bisnortilidine is a weak inhibitor of CYP3A4 and CYP2B6, a strong inhibitor of CYP2D6, but not an inhibitor of CYP2C19. Our study demonstrated that nortilidine is metabolised via the same CYP isozymes as the prodrug tilidine, whereas the formation of bisnortilidine appears to be the rate-limiting step in the metabolism of tilidine. Pharmacokinetic interactions can be expected with inhibitors or inducers of CYP3A4, CYP2C19 or CYP2B6.